2014
DOI: 10.1186/s12888-014-0352-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in circadian/seasonal rhythms and vegetative functions are related to suicidality in DSM-5 PTSD

Abstract: BackgroundAlterations in rhythmicity and vegetative functions have been reported as correlates of suicidality, particularly in patients with mood disorders. No investigation has addressed their impact on patients with post-traumatic stress disorder (PTSD). Aim of the present study was to fulfill this gap.MethodsSixty-five out- and inpatients with DSM-5 PTSD were assessed by using the Mood Spectrum-Self Report-Lifetime Version (MOODS-SR), a questionnaire for lifetime mood spectrum symptomatology including alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 72 publications
2
33
0
Order By: Relevance
“…37 In a smaller sample of both inpatient and outpatient participants, results of patients with PTSD with both a sleep rhythmicity subscale (with higher values indicting greater rhythmicity problems) and a sleep disturbance scale were associated with SI; only rhythmicity remained significant in regression models. 38 Among inpatient and outpatient participants in substance abuse programs in Poland, insomnia severity over a 1-month period followed by a 6-month period was associated with SI in unadjusted models and "past month insomnia" severity remained significant in models adjusting for psychopathology. 41 Among 44 inpatient participants with recurrent depressive disorder, the presence of nightmares was associated with suicide risk from a depression scale; no such findings were observed in eight patients with bipolar disorder.…”
Section: Cross-sectional Studiesmentioning
confidence: 98%
“…37 In a smaller sample of both inpatient and outpatient participants, results of patients with PTSD with both a sleep rhythmicity subscale (with higher values indicting greater rhythmicity problems) and a sleep disturbance scale were associated with SI; only rhythmicity remained significant in regression models. 38 Among inpatient and outpatient participants in substance abuse programs in Poland, insomnia severity over a 1-month period followed by a 6-month period was associated with SI in unadjusted models and "past month insomnia" severity remained significant in models adjusting for psychopathology. 41 Among 44 inpatient participants with recurrent depressive disorder, the presence of nightmares was associated with suicide risk from a depression scale; no such findings were observed in eight patients with bipolar disorder.…”
Section: Cross-sectional Studiesmentioning
confidence: 98%
“…In 4 of these studies, a significant increase in suicide risk was found for the evening-type chronotype [3,[47][48][49].…”
Section: Adultsmentioning
confidence: 99%
“…The study conducted by Dell' Osso et al with post-traumatic stress disorder patients [49] showed an association of sleep rhythmicity dysregulations with suicidal ideation, but not with suicide attempts. The nature of the associations was maintained after adjusting for depression.…”
Section: Adultsmentioning
confidence: 99%
See 2 more Smart Citations